2014
DOI: 10.1186/1472-6920-14-151
|View full text |Cite
|
Sign up to set email alerts
|

A survey of factors influencing career preference in new-entrant and exiting medical students from four UK medical schools

Abstract: BackgroundWorkforce planning is a central issue for service provision and has consequences for medical education. Much work has been examined the career intentions, career preferences and career destinations of UK medical graduates but there is little published about medical students career intentions. How soon do medical students formulate careers intentions? How much do these intentions and preferences change during medical school? If they do change, what are the determining factors? Our aim was to compare m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
98
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 52 publications
(60 reference statements)
12
98
2
4
Order By: Relevance
“…In studies with medical students, the female presence ranges from 22.4% in the medical course at the Federal University of Espírito Santo 14 to 50.2% at the State University of Londrina, 9 while in foreign studies this ranges from 48% in the United States 49 to 67.1% in the United Kingdom. 50 Given the different values expressed by women and men in relation to their reasons for choosing the profession, the study raises new investigations into the possible impacts of the feminization of medicine in Brazil. Will medicine become a profession focused more on care and less valued for professional success?…”
Section: Discussionmentioning
confidence: 99%
“…In studies with medical students, the female presence ranges from 22.4% in the medical course at the Federal University of Espírito Santo 14 to 50.2% at the State University of Londrina, 9 while in foreign studies this ranges from 48% in the United States 49 to 67.1% in the United Kingdom. 50 Given the different values expressed by women and men in relation to their reasons for choosing the profession, the study raises new investigations into the possible impacts of the feminization of medicine in Brazil. Will medicine become a profession focused more on care and less valued for professional success?…”
Section: Discussionmentioning
confidence: 99%
“…Two UK studies that have examined this topic indirectly found no obvious relationship. 49,50 However, the influence of PES on career decisions was only a minor consideration in both of these and more work is needed to fully explore this area. Until this occurs, the difference in the rate of high PES between the two cohorts presents an unknown variable when attempting to compare Ghanaian and UK medical students' career decisions.…”
Section: Demographic Differences Between Ghanaian and Uk Studentsmentioning
confidence: 99%
“…However, the results from this study differ from other studies that show a high number of students pursuing a career in anaesthesia. 6 The reasons for anaesthesia not being chosen by the majority of students are related to duration of clerkship, stress, danger and risk associated with anaesthesia. The majority of the students (41.7%) who chose paediatrics as a career indicated that they enjoyed their clerkship in paediatrics while six (23.1%) students of surgery indicated the same reasons for their choice.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Men are typically more attracted by technical challenges, prestige and learning potential. 6 In line with this, females were found to opt for careers in community-based areas and social medicine, whereas males were found to be more inclined to hospital-based specialties. This is evidenced in the current study, although the results of this study could not substantiate the influence of gender on specialty preferences.…”
Section: Discussionmentioning
confidence: 99%